Poly lactic‐co‐glycolic acid‐alginate nanocarrier for efficient drug delivery to liver cancer cells - Mahsa Hoseinzadeh; Mohammad Javad Mokhtari; Farshid Kafilzadeh; Javad Mohammadnejad; Yaghoob Taheri (IET Nanobiotechnology)
Abstract Efficient drug delivery systems (DDSs) can potentially replace with conventional modalities in cancer therapy, like liver cancer. In this study, a novel folic acid (FA)‐functionalised and alginate (Alg)‐modified poly lactic‐co‐glycolic acid (PLGA) nanocomposite was developed for delivery of doxorubicin (Dox) to HepG2 and Huh7 liver cancer cells. After synthesising the nanocarrier, several analytical devices, including FT‐IR, DLS, TGA, and TEM, were employed for its characterisation. Nano‐metric size (55 and 85 nm in diameter), close to neutral surface charge, semi‐spherical morphology, and successful synthesis were approved. Dox entrapment efficiency was determined near 1%, and sustained and pH‐sensitive drug release behaviours of nanocarrier were ascertained for DDS. Afterwards, the cell viability test was carried out to study the HepG2 and Huh7 cells suppression capability of FA‐PLGA‐Dox‐Alg. About 12% and 10% cell viabilities were observed in HepG2 and Huh7 cancer cells after 24 h treatment with 400 nM concentration of FA‐PLGA‐Dox‐Alg nanocarrier respectively. The IC50 value was observed for 100 nM after 24 h of treatment in cancer cells. These data have indicated that fabricated nanocarrier could be promising DDS against liver cancer and replace with conventional approaches in cancer treatment, like chemotherapy.